Comparing the effectiveness of preparatory activities that help undergraduate students learn from instruction. (December 2022) - Trninic, Dragan; Sinha, Tanmay; Kapur, Manu
Abstract: Students can learn better from instruction after first engaging in activities that prepare them to learn (Kapur, 2016; Loibl, Roll, & Rummel, 2017; Schwartz & Bransford, 1998). In this study, we compare the effectiveness of four activities that prepare university students to learn from instruction. We use productive failure, an established instructional design, as the baseline preparatory condition. In productive failure, students generate solutions to challenging but accessible problems, which serves as preparation for formal instruction. We compare this approach with three alternative preparatory activities: contrasting a correct and an incorrect solution, sensemaking of the correct solution only, and studying a fully worked-out example of the correct solution. Despite the differences in preparatory activities, participants on average performed nearly identically on most of the process and outcome measures. In universities, or with similarly advanced learners, a variety of activities may be equally effective at preparing students to learn from instruction. Highlights: Students can learn better from instruction after engaging in preparatory activities. Preparatory activities are typically investigated with novice learners. Four preparatory activities were compared at the university level. Surprisingly, there were few appreciable differences. Variety of preparatory activities may be similarly effective for advanced learners.